STRESS AMONG MEDICAL STUDENTS - A GLOBAL CONCERN - Haque, Mainul (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Stress is any exasperating and infuriating "emotional experience accompanied by predictable biochemical, physiological and behavioral changes" [1]. At many occasions stress can be useful at times, bring into being a boost that offers the drive and energy to help individuals get through situations like exams or work deadlines. Nevertheless, a life-threatening amount of stress can have health concerns and negatively upset the immune, cardiovascular, neuroendocrine and central nervous systems [2].